Efficacy of Rose Oil Soft Capsules on Clinical Outcomes in Ulcerative Colitis: A Pilot Randomized, Double-Blinded, Placebo-Controlled Clinical Trial: - Pasalar, Mehdi; Tavakoli, Ali; Shirzad, Meysam; Taghavi, Alireza; Fattahi, Mohammadreza; Ahmadian-Attari, Mohammadmahdi; Mohammad Taghizadeh, Leila; Rostami Chaijan, Mahsa; Sedigh Rahimabadi, Masih; Akrami, Rahimeh (Galen Medical Journal, 2019)
Background: Ulcerative colitis is the most common form of inflammatory bowel disease worldwide, which presents with superficial ulcers in the rectum and colon. The aim of this study was to assess the effectiveness of rose oil soft capsules over placebo on the clinical outcomes in moderate to severe ulcerative colitis. Materials and Methods: This study was a pilot randomized, double-blind clinical trial, and the 40 patients were assigned into rose oil and placebo groups (n=20 per group). All patients were instructed to use their prescribed two soft capsules three times daily for two months. The clinical symptoms, quality of life the patients, and calprotectin level were evaluated via partial Mayo clinic score, irritable bowel disease questionnaire (IBDQ-9), and calprotectin kit as primary outcome measures. Results: The mean age of the participants was 41Â±10 years. Most of them (53.6%) were male, and the remaining (46.4%) were female. The demographic and baseline data showed no differences between the two groups. Partial Mayo clinic scores decreased in both groups after the treatment, but the difference between the rose oil and placebo groups was not statistically significant (P=0.99). IBDQ-9 score also increased in both interventions before and after the treatment (P=0.012), though the differences between these two groups were not statistically significant (P=0.61). There were no significant differences between the two study groups either in terms of calprotectin level (P=0.219). Conclusion: This study showed that rose oil might improve ulcerative colitis clinical outcomes, but for a better evaluation, it is imperative to conduct experiments with a large sample size and longer follow-up observation. [GMJ.2019;8:e1307]